Homotopy Analysis Solution for Magnetohydrodynamic Squeezing Flow in Porous Medium - Inayat Ullah; M. T. Rahim; Hamid Khan; Mubashir Qayyum (Advances in Mathematical Physics)
The aim of the present work is to analyze the magnetohydrodynamic (MHD) squeezing flow through porous medium using homotopy analysis method (HAM). Fourth-order boundary value problem is modeled through stream function ψ(r,z) and transformation ψ(r,z)=r2f(z). Absolute residuals are used to check the efficiency and consistency of HAM. Other analytical techniques are compared with the present work. It is shown that results of good agreement can be obtained by choosing a suitable value of convergence control parameter h in the valid region Rh. The influence of different parameters on the flow is argued theoretically as well as graphically.